Cyclops Syndrome After Anterior Cruciate Ligament (ACL) Reconstruction: A Rehabilitation Report with Molecular Mechanisms Strategies - Tita Rachma Ayuningtyas; Miftakhul Khoiriyah (Universitas Negeri Surabaya, 2026)
Background: Cyclops syndrome is a recognized complication after anterior cruciate ligament (ACL) reconstruction, characterized by fibrous nodule formation in the intercondylar notch leading to painful restriction of knee extension. While mechanical obstruction has been considered the primary cause, emerging evidence suggests that molecular dysbalance may also contribute to lesion development. Objectives: This case report aims to describe the clinical symptoms of a patient with cyclops syndrome following ACL rupture and to explore whether these manifestations arise predominantly from mechanical obstruction or molecular dysregulation. Methods: A descriptive case report design was employed. Patient symptoms were assessed through clinical examination, range of motion measurement, pain evaluation, and functional assessment. Magnetic resonance imaging (MRI) and arthroscopic evaluation confirmed the presence of a fibrous nodule. Literature review was integrated to contextualize findings within known molecular pathways, including cytokine imbalance and fibroblast activation. Results: The patient presented with painful loss of terminal knee extension, stiffness, and mechanical catching during movement. Imaging confirmed a fibrous nodule consistent with cyclops lesion. Symptom analysis suggested contributions from both mechanical obstruction and molecular dysbalance, with clinical features aligning with reported cytokine-mediated fibrosis and extracellular matrix remodeling. Conclusion: Cyclops syndrome after ACL reconstruction is a multifactorial condition, with symptoms arising from both mechanical and molecular mechanisms. Early recognition of extension deficits, precise surgical technique, and structured physiotherapy are essential for management. Consideration of molecular pathways may inform future therapeutic strategies, integrating anti-fibrotic or cytokine-modulating interventions to complement mechanical treatment.